Cloud based air quality monitoring with notification through telegram / Hajar Masturah Sulaiman - Sulaiman, Hajar Masturah (2019)
Air pollution can caused health problems to people that breathe the polluted air. They might start to coughing, wheezing and the heart feel tight. People will be affected as they will feel hard to breathe especially those with asthma. The polluted gases can make the lung irritating and the airways feel tight. They will have short breathe and can caused death. Sometimes they forget where they put the inhaler. This system can detect the quality of the air by using gas sensor. Next, it will give notification to user and they can take precaution steps before getting any asthma attacks. By using ESP8266 Wi-Fi module, this system can provide notification to the user through Telegram Bot in real-time. By using this module also, they can monitor the amount of polluted gases in the air in Cloud. The Cloud also can provide space for storing the data collected by the sensors.